A systematic design approach for XML-view driven web document warehouses - Nassis, V.; Rajugan, Rajagopal; Dillon, Tharam S.; Rahayau, W. (Springer, 2005)
EXtensible Markup Language (XML) has emerged as the dominant standard in describing and exchanging data among heterogeneous data sources. The ever increasing presence of XML web contents in large volumes creates the need to investigate Web Document Warehouses (WDW) and Web Document Marts, as a means of archiving and analysing large web contents for contextaware web/business intelligence. To address such an issue, in this paper, we focus on intuitively adopting our pervious work on XML-view based XML Document Warehouse design for building a Web Document Warehouse (WDW). To demonstrate this, here, we carryout a systematic approach to conceptual modelling and transformation of the warehouse conceptual model into a logical/schema (XML Schema) model and an in-depth analysis of deriving and querying context-aware WDW dimensions.